2020
DOI: 10.3390/ma13061375
|View full text |Cite
|
Sign up to set email alerts
|

Bead-Shaped Mesoporous Alumina Adsorbents for Adsorption of Ammonia

Abstract: It is of great importance to remove toxic gases by efficient methods for recovering the atmosphere to safe levels. The adsorption of the toxic gas molecules on solid adsorbents is one of the most useful techniques because of its simple operation and economic feasibility. Here, we report the uniform Bead-Shaped Mesoporous Alumina (BSMA) with tunable particle size for use as an adsorbent for removal of toxic ammonia. The BSMA particles with tunable diameters were synthesized by means of a sol-gel reaction of Al(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The powder-type adsorbents can be easily lost or blocked, which will disturb the operation process. The morphology of adsorbents is an essential parameter for the adsorption in industry; millimeter-sized spherical adsorbents are the most favorable for adsorption, according to the literature [ 7 , 8 ], since this kind of adsorbent can be easily handled, separated, and recycled. This is the reason why millimeter-sized, bead-type adsorbents were popularly used in the practical adsorption column [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The powder-type adsorbents can be easily lost or blocked, which will disturb the operation process. The morphology of adsorbents is an essential parameter for the adsorption in industry; millimeter-sized spherical adsorbents are the most favorable for adsorption, according to the literature [ 7 , 8 ], since this kind of adsorbent can be easily handled, separated, and recycled. This is the reason why millimeter-sized, bead-type adsorbents were popularly used in the practical adsorption column [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although they possess the merits of high efficiency and low cost, they also suffer from the drawbacks of heavy energy-consumption, corrosion, and waste of NH 3 resources. 10,11 Besides, various porous materials, including activated carbon, 12,13 zeolite, 14,15 alumina 16,17 and metal-organic frameworks, 18 have been demonstrated as adsorbents for efficient NH 3 removal, and there has been remarkable progress on adsorption of NH 3 in terms of adsorption capacity or adsorption kinetics. 19 Solid adsorbents have the advantages of being energy saving during the regeneration process and easy operation compared to liquid absorbents.…”
Section: Introductionmentioning
confidence: 99%
“…were prepared using chitosan/PVA, who figured out that calcination temperature directly affects the pore volume, average pore size, and specific surface areas 23 . Kim et al 24 . prepared Bead‐Shaped Mesoporous Alumina by adding the alumina precursor to the aqueous chitosan solution and found that varying the mole ratio of chitosan‐to‐alumina significantly influences the size of beads.…”
Section: Introductionmentioning
confidence: 99%